The three paths Chinese scholars have followed in studying the Marx-Hegel-relationship – and a proposal for a new path - Tao Tan (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2023)
Per questa sezione non è richiesto un abstract.